1985
DOI: 10.1111/j.1365-2141.1985.tb02989.x
|View full text |Cite
|
Sign up to set email alerts
|

Anticardiolipin antibodies in autoimmune thrombocytopenic purpura

Abstract: Using a recently devised solid phase radioimmunoassay to detect anticardiolipin antibodies, we report the presence of these antibodies in 30 of 96 patients with chronic autoimmune thrombocytopenic purpura (AITP). IgG anticardiolipin antibody levels were elevated in 14 patients and IgM anticardiolipin antibody levels were elevated in 27 patients. We suggest that these antibodies may mediate peripheral platelet destruction by binding to phospholipids in the platelet membrane. It is also conceivable that the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
3
3

Year Published

1987
1987
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(87 citation statements)
references
References 6 publications
(1 reference statement)
3
76
3
3
Order By: Relevance
“…In this study, we investigated the frequency of APAs in patients with ITP, and we found that more than one third of these patients (37.8%) had APAs at the time of diagnosis, a finding consistent with other reports. 4,5 Although many researchers have suggested that APA positivity is not correlated with the development of APS in patients with ITP, 5,7 there are case reports on the development of APS in patients who initially presented with ITP. 14 In this study, we found that 14 of 31 patients (45.1%) who were persistently positive for APAs developed APS in the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we investigated the frequency of APAs in patients with ITP, and we found that more than one third of these patients (37.8%) had APAs at the time of diagnosis, a finding consistent with other reports. 4,5 Although many researchers have suggested that APA positivity is not correlated with the development of APS in patients with ITP, 5,7 there are case reports on the development of APS in patients who initially presented with ITP. 14 In this study, we found that 14 of 31 patients (45.1%) who were persistently positive for APAs developed APS in the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators suggest that antibodies other than APA, mainly those against GPIIb-IIIa and other membrane GPs, cause thrombocytopenia in patients with APS. 2,3 Although Harris et al 4 found anticardiolipin antibodies (ACAs) in 30% of ITP patients at the time of diagnosis, many researchers have questioned the clinical significance of this observation. Elevated levels of APAs are common in ITP and often do not change significantly with immunosuppressive therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombocytopenia in SLE is strongly associated with aPL (1,(20)(21)(22)(23). The IgG isotype of aPL has been detected in 72% of SLE patients with thrombocytopenia.…”
Section: Thrombocytopenia and Hemolytic Anemiamentioning
confidence: 99%
“…However, platelet activation should be a pre-requisite for APLA-platelet binding because it leads to the exposure of negatively charged phospholipids on the platelet surface. 10 Nojima et al 11 showed that plasma containing both anticardiolipin and LA increased platelet activation in the presence of low concentrations of ADP, suggesting that these antibodies promote platelet activation, thus contributing to the pathogenesis of arterial thrombosis and thrombocytopenia. Jy et al 9 found that platelet activation predisposes to thrombosis in the presence of chronic EC activation in subjects positive for APLA.…”
Section: 3mentioning
confidence: 99%